Rove beetles collected with carrion traps (Coleoptera: Staphylinidae) in Quercus forest of Cerro de García, Jalisco and Quercus, Quercus-pine, and pine forests in other jurisdictions of Mexico - Rodríguez, William David; Navarrete-Heredia, José Luis; Klimaszewski, Jan (Zootaxa, 2018)
We present the species diversity of rove beetles (Coleoptera: Staphylinidae) collected with carrion baited traps in Quercus forests of Cerro de García, Jalisco, and provide a compilation of published species records in Quercus, Quercus-pine and pine forests in other jurisdictions of Mexico. This work includes taxonomic notes, information on species phenology, distribution, and their occurrence in Cerro de García (if applicable), and other jurisdictions of Mexico. In Cerro de García, 75 species were collected in total, of which 16 are shared with other Quercus forests in different locations, and 9 species are provided with new habitat data. The remaining individuals were only determined to morphospecies. In Mexico, there are 77 known species of rove beetles collected with carrion traps (determined to species or near species) and recorded from Quercus, Quercus-pine and pine forests. These species belong to 30 genera, 11 tribes and 10 subfamilies. This study provides biological information on Mexican rove beetles captured with carrion traps and highlights the importance of rove beetles as indicator species of habitat change for conservation analysis, forestry, agronomy and forensic sciences studies.